2021
DOI: 10.1002/chem.202103487
|View full text |Cite
|
Sign up to set email alerts
|

Coordinatively Unsaturated Amidotitanocene Cations with Inverted σ and π Bond Strengths: Controlled Release of Aminyl Radicals and Hydrogenation/Dehydrogenation Catalysis

Abstract: Cationic amidotitanocene complexes [Cp2Ti(NPhAr)][B(C6F5)4] (Cp=η5‐C5H5; Ar=phenyl (1 a), p‐tolyl (1 b), p‐anisyl (1 c)) were isolated. The bonding situation was studied by DFT (Density Functional Theory) using EDA‐NOCV (Energy Decomposition Analysis with Natural Orbitals for Chemical Valence). The polar Ti−N bond in 1 a–c features an unusual inversion of σ and π bond strengths responsible for the balance between stability and reactivity in these coordinatively unsaturated species. In solution, 1 a–c undergo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…We have previously shown that amidotitanocene cations readily decompose by Ti−N bond homolysis under visible light irradiation (Scheme 3). 9 This behavior is typical of LMCT reactivity at a 3d metal, 39 and it is exacerbated by the well-documented reductibility of d 0 titanocene derivatives on the one hand 40−42 and the strong basicity of amides on the other hand. 43 The resulting Ti(III) complex can be trapped in the presence of THF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that amidotitanocene cations readily decompose by Ti−N bond homolysis under visible light irradiation (Scheme 3). 9 This behavior is typical of LMCT reactivity at a 3d metal, 39 and it is exacerbated by the well-documented reductibility of d 0 titanocene derivatives on the one hand 40−42 and the strong basicity of amides on the other hand. 43 The resulting Ti(III) complex can be trapped in the presence of THF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Complex 1d was characterized by single crystal X-ray diffraction (XRD) analysis, which revealed (as expected) a κ 2 -N,N′ coordination mode for the amide (Figure ). Surprisingly, the Ti–N1 distance (amide) is only slightly shorter (0.046 Å) than the Ti–N2 distance (pyridine); it is also considerably longer (0.087 Å) than the Ti–N1 distance in Ib , which was previously characterized by XRD . Together, these observations indicate that the additional electron donation from the pyridine ring weakens the interaction between the metal and the amide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dehydrocoupling between amines and hydrosilanes seems to be the most attractive route, due to the formation of H 2 as the by-product (Figure 1, c). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Unfortunately, this approach is completely impractical for the preparation of a highly important trimethylsilyl-protecting group, due to the pyrophoricity of gaseous Me 3 SiH. Moreover, the control of the chemoselectivity for Si-H/N-H dehydrocoupling has proved to be challenging due to the possible formation of several products including polymeric silazanes and a mixture of mono-and di-silylated amines.…”
mentioning
confidence: 99%